Panama : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2014)
This report assesses the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) in Panama. Panama is vulnerable to money laundering from a number of sources, including drug trafficking and other predicate crimes committed abroad-such as fraud and financial and tax crimes. Panama has criminalized money laundering and terrorism financing, but its AML/CFT framework is not fully in line with the FATF recommendations. Some requirements form combating the financing of terrorism are included in subsidiary instruments, but these appear to go beyond the AML Law and, therefore, are inconsistent with the legal principles established under the Constitution. There are inadequate statistics on money laundering investigations, prosecutions, and convictions to properly assess the effectiveness of implementation of the legislation.